Intuitive digital computer basics : an introduction to the digital world. - Frederiksen, Thomas M. (New York, United States of America : McGraw-Hill, Inc., 1988)
"Written to appeal to nonelectronics professionals as well as electronics engineers and managers, this up-to-the-minute guide provides an intuitive insight into digital computer concepts. With it, you'll be able to understand the technical principles that are behind what is happening; no prior experience in digital electronics is necessary. In easy-to understand language, Intuitive Digital Computer Basics clearly and concisely explains everything from basic circuit concepts to logic gates ...TTL and CMOS technology ... binary numbers ... microprocessors ... computer architectures ... and programming. Here you'll get detailed coverage of the essentials-such as understanding numbers and calculations, the use of voltmeters, and basic electronic circuitry-as well as detailed discussions of voltage, dc circuit components, digital concepts, and the techniques of digital computers. The book also describes what the future holds in terms of gate arrays, cell arrays, computer networking, electronic offices and homes, artificial intelligence, robots, and role manipulation." (Copied from the paste).
Preface. Acknowledgments. Chapter 1. Some preliminary topics. Chapter 2. Voltage: The pressure of the electrons. Chapter 3. Circuit Components operating with direct current. Chapter 4. Learning to think digital. Chapter 5. The techniques of digital computers. Chapter 6. A look into the future. Index.
Keywords: ELECTRONIC DIGITAL COMPUTERS; ELECTRONIC DIGITAL COMPUTERS -- DESIGN; ELECTRONIC ENGINEER; MICROPROCESSORS; COMPUTER ARCHITECTURES; PROGRAMMING; COMPUTER NETWORKING; ARTIFICIAL INTELLIGENCE; INTEGRATED CIRCUITS